THE INFLUENCE OF ROM AND MCIM ON THE ABILITY OF JOINT MOVEMENT IN TRADITIONAL FISHERMAN-DIVERS - Reni Devianti Usman; Dwi Purnama Putri; Dian Yuniar Syanti Rahayu (POLTEKKES KEMENKES JAYAPURA, 2022)
Decompression diseases can provide manifestations that vary from mild to those that can cause disability and even life-threatening. This condition significantly affects the quality of life of sufferers and impacts meeting their personal care needs and productivity as the head of the family. This condition also impacts the family economy, affecting the lives of other family members. The purpose of the study was to see the effect of a range of motion exercise (ROM) therapy and modified constraint-induced movement (MCIM) on the ability of a joint range of motion in traditional fishermen who experience paralysis due to decompression disease. This exercise aims to improve the power of the limb that has paralysis. The combination of these two therapies can aid in preventing contractures, enhance the ability of a joint range of motion and increase muscle strength. The type of research in this study is a quasi-experiment with design, or the research design carried out in this study is the pretest-posttest one-group design. The population in this study was all Traditional Divers in Soropia District. Sampling in this study with purposive sampling technique is a traditional diver who experiences paralysis. Data analysis management uses coding, scoring, and tabulating by looking at the frequency distribution of all variables. The analysis is a univariate and bivariate analysis with a dependent T-test. The study results were average range motion of the pre-test joints of 15.53 with a standard deviation of 2,232, and the middle range of motion of the joints in the post-test was 14.67 with a standard deviation of 1,915. The difference between the average pre-test and post-test is 0.86. With the P-Value value obtained a value of 0.001, more minor than the alpha of 0.05, it can be concluded that there is a significant influence of the combination of therapies on the range of joint motion in traditional divers who experience paralysis. The results can figure that there are substantial differences before and after training for alternative nursing intervention. Keywords: MCIM, Paralysis, ROM, Traditional diver fisherman